Dampak gawai dan status gizi pada remaja di SMK Negeri 1 Lhoknga dan Poltekkes Aceh 2019 - Teuku Jamni (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: Gadgets are also seen as a form of technological development that is used equally across all ages. the forms of devices used to communicate with adolescents are of course very many and varied. The use of gadgets in adolescents is associated with high, screen-time nutritional status, low activity levels, and causes eating patterns to be incompatible with recommendations so that in the long run it can affect nutritional status.Purpose: The purpose of this study was to analyze how much impact the device has and the nutritional status of adolescents.Method: The research method used is descriptive method, observational study design with cross-sectional design with research subjects adolescents aged 12-21 years, amounting to 200 samples consisting of polytechnic students, kindergarten semester 1 odd, nutritional, dental and sanitarian, and Lhoknga Vocational students. Data duration of the use of the device is obtained from a structured questionnaire that has been validated, nutritional status is determined based on the z-score body mass index of age (BMI / U), data collection techniques using questionnaires and supporting techniques are interviews and documentation.Results: The results showed a very high Gawai impact on adolescent gadgets (71%), the category of nutritional status with Skinny (Z-Score IMT / U <-2 to <3 SD) (94%). while eating patterns are not appropriate (55%). The results of the analysis show the impact between the use of devices and nutritional status (p < 0.05)Conclusion: The use of gadgets has a positive impact in improving the nutritional status of adolescents at SMK Negeri 1 Lhoknga and adolescents at the Poltekkes of the Ministry of Health in Aceh. Suggestions, conduct counseling on the wise use of devices, regulations and legal sanctions for device users, ethics for using devices in Sharia law, and using devices positively.